Lean on me : surviving women make the transition to freedom - Wright, Ruth Tamaria (2004)
Throughout history, men have abused women by treating them as property, enforcing power, violence and sexual perversion with the intention of attaining and maintaining ownership and societal control. This same sense of ownership and control has been instrumental in creating an expectation of behavior by women and giving power and control to men to enforce the demands that have been placed upon women leading to the socialization of women's victimization by male violence. The prevalence of domestic intimate partner violence is on the rise at one million incidents in each year of the decade with 97,941 females incarcerated at year end of 2002. There is little research connecting former incarcerated females, intimate partner violence, and using community involvement to lower rates of recidivism. Hence, this study proposes to explore, by comparing and contrasting, successful transitional outcomes between females who have been incarcerated and abused versus females who have been abused